Mentoring and MSME Machinery in Start-up Business Planning: A Thai Snack Case Study - Sutisnawati, Yayah; Syafei, M. Yani; Srisuk, Prattana; Irawan, Nico; Astillero, Marlon Rael (PT Inovasi Pratama Internasional, 2025)
This study explores the role of mentoring and the utilization of MSMEs machinery as strategic factors in preparing effective business plans for young start-ups, with a focus on Thai snack micro, small, and medium enterprises (MSMEs). Mentoring is examined as a source of guidance, knowledge transfer, and confidence building, while UMKM machinery is considered as a technological variable that enhances production efficiency and product quality. Using a case study approach, data were collected through interviews, observations, and document analysis from selected Thai snack MSMEs. The findings indicate that mentoring significantly improves entrepreneurs’ ability to structure comprehensive business plans, identify market opportunities, and manage risks. Simultaneously, the adoption of UMKM machinery contributes to operational scalability and competitiveness, enabling young start-ups to meet market demand more effectively. The integration of mentoring and machinery adoption provides a synergistic effect, resulting in stronger strategic planning and sustainable business growth. This study highlights the importance of combining human capital development with technological adoption to support the success of young entrepreneurs in the MSME sector.